PERAN INFORMASI AKUNTANSI DIFERENSIAL DAN CAPITAL BUDGETING PADA BAKSO SW DI TARAKAN - Ferica Christinawati Putri (Pusat Riset dan Inovasi Nasional, 2021)
This study’s goal to see the most appropriate decisions that can be taken by management in making decisions or make their own meatballs using different accounting information by comparing the differential costs that will be incurred when making it yourself and managing and managing the feasibility of fixed investment planning that will still be purchased by SW meatball. The data stage is carried out to obtain data related to differential costs and investment planning, then the data will be processed for further analysis and drawing conclusions. The results showed that the better decision was made by Bakso SW by making their own meatballs because they were more concerned about costs and benefits compared to suppliers and that SW Meatballs could invest in fixed assets to gain profit by adding a new grinding machine when the economy of the previous grinding machine had run out.